2023
DOI: 10.3390/molecules28176411
|View full text |Cite
|
Sign up to set email alerts
|

Phytocompounds from Amazonian Plant Species against Acute Kidney Injury: Potential Nephroprotective Effects

Alberto Souza Paes,
Rosemary de Carvalho Rocha Koga,
Priscila Faimann Sales
et al.

Abstract: There are several Amazonian plant species with potential pharmacological validation for the treatment of acute kidney injury, a condition in which the kidneys are unable to adequately filter the blood, resulting in the accumulation of toxins and waste in the body. Scientific production on plant compounds capable of preventing or attenuating acute kidney injury—caused by several factors, including ischemia, toxins, and inflammation—has shown promising results in animal models of acute kidney injury and some pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 171 publications
(192 reference statements)
0
0
0
Order By: Relevance
“…In fact, recent studies by [7] revealed that the HPLC-QTOF-MS/MS analysis of E. alata seeds showed various phytochemicals, including flavonoids, sphingolipids, and ephedrine derivatives. Natural antioxidants are capable of reducing free radical injuries by acting directly as a free radical scavenger and/or indirectly by activating enzymatic (SOD, CAT and GSH-Px) and nonenzymatic (GSH) antioxidant systems, which reduce lipid peroxidation in animals [40][41][42][43]. In addition, these natural compounds play an effective function in preserving mitochondrial homeostasis and therefore protecting against oxidative damage [44].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, recent studies by [7] revealed that the HPLC-QTOF-MS/MS analysis of E. alata seeds showed various phytochemicals, including flavonoids, sphingolipids, and ephedrine derivatives. Natural antioxidants are capable of reducing free radical injuries by acting directly as a free radical scavenger and/or indirectly by activating enzymatic (SOD, CAT and GSH-Px) and nonenzymatic (GSH) antioxidant systems, which reduce lipid peroxidation in animals [40][41][42][43]. In addition, these natural compounds play an effective function in preserving mitochondrial homeostasis and therefore protecting against oxidative damage [44].…”
Section: Discussionmentioning
confidence: 99%